KINAESTHETIC LEARNING STYLE AND ITS USAGE IN LEARNING PROCESS IN BASIC SCHOOL - Jonāne, Lolita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The aim of the research is to explore the possibilities and methodological solutions of using kinaesthetic teaching style in the teaching/learning process in basic school and its impact on pupil involvement in learning activities and attainment of goals. Qualitative and quantitative methods - experienced teacher’s survey and student-trainee survey after observation and analysys of lessons at school are used during the study. It is concluded that: 1)the kinesthetic style of learning involves different forms - tactile, movement-based learning, warm-up and relaxation exercises; 2)it is applicable at all stages of education and in teaching/ learning and extra-curricular activities; 3) it is effective during the classroom if it is consistent with the age of the pupils and the learning content. The survey concluded that majority of surveyed teachers positively evaluate the kinesthetic teaching/ learning style and quite often apply it in their lessons according to their competence.